Pola Komunikasi Interpersonal Antara Pembina dan Santri dalam Metode Menghafal Al-Qur’an - Fatihatul Jannah; Mokhamad Baharun; Wisri (Maddah : Jurnal Komunikasi dan Konseling Islam, 2024)
This article discusses the interpersonal communication patterns of coaches towards students in the method of memorizing the Al-Qur'an at the Salafiyah Syafi'iyah Sukorejo Islamic Boarding School. Researchers used qualitative methods with a descriptive approach. Communication is needed by every individual in every aspect of life, including memorizing the Koran. Without good communication there will be difficulties in the memorizing process. Because communication is a symbolic transaction that requires people to regulate the environment by building relationships between each other through exchanging information to strengthen attitudes and behavior and trying to strengthen them. This is also what the supervisors do for students in memorizing the Al-Quran at the Salafiyah Syafi'iyah Sukorejo Islamic Boarding School. This article was explored using descriptive qualitative methods. The results obtained in this research show that interpersonal communication patterns in the method of memorizing the Al-Qur'an used by coaches for students include group communication, interpersonal communication and intrapersonal communication. The interpersonal communication pattern is dominant because it is very relevant for coaches to use for students in teaching them to memorize the Qur'an.